2013
DOI: 10.1007/s00253-013-5421-9
|View full text |Cite|
|
Sign up to set email alerts
|

The attractive recombinant phytase from Bacillus licheniformis: biochemical and molecular characterization

Abstract: The phyL gene encoding phytase from the industrial strain Bacillus licheniformis ATCC 14580 (PhyL) was cloned, sequenced, and overexpressed in Escherichia coli. Biochemical characterization demonstrated that the recombinant enzyme has an apparent molecular weight of nearly 42 kDa. Interestingly, this enzyme was optimally active at 70-75 °C and pH 6.5-7.0. This enzyme is distinguishable by the fact that it preserved more than 40 % of its activity at wide range of temperatures from 4 to 85 °C. This new phytase d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…KHU-10 phytase (10 mM CaCl 2 ) [30] , and recombinant phytase (rePhyCm) [34] . However, Gulati et al [17] , El-Toukhy et al [35] , Borgi et al [36] , and Nuñal et al [37] reported different findings for B. laevolacticus , B. subtilis MJA, B. licheniformis ATCC 14580 (PhyL), and different Bacillus strains, respectively. B. amyloliquefaciens US573 had a similar optimum pH of 7.5, but higher optimum temperature (70 °C) than B. subtilis B.S.46 [31] .…”
Section: Resultsmentioning
confidence: 99%
“…KHU-10 phytase (10 mM CaCl 2 ) [30] , and recombinant phytase (rePhyCm) [34] . However, Gulati et al [17] , El-Toukhy et al [35] , Borgi et al [36] , and Nuñal et al [37] reported different findings for B. laevolacticus , B. subtilis MJA, B. licheniformis ATCC 14580 (PhyL), and different Bacillus strains, respectively. B. amyloliquefaciens US573 had a similar optimum pH of 7.5, but higher optimum temperature (70 °C) than B. subtilis B.S.46 [31] .…”
Section: Resultsmentioning
confidence: 99%
“…The apparent K m , V max , k cat and catalytic efficiency k cat /K m were 1.125 mM, 27.71 U/mg, 1687.37 min −1 and 1499.88 mM −1 min −1 respectively. The catalytic efficiency of PHY US573 was higher than other phytases characterized from the genus Bacillus [35][36][37] and other bacterial genera like Erwinia carotovora, Pedobacter nyackensis MJ11 CGMCC 2503, Klebsiella pneumoniae and E. coli [38,39].…”
Section: Substrate Specificity and Kinetic Studies Of Phy Us573mentioning
confidence: 99%
“…Coban et al (2015) enhanced the phytase production in SmF by using a novel fermentation technique by testing the effect of the various microparticles on A. ficuum. Borgi et al (2014), characterized the recombinant phytase from B. licheniformis ATCC 14580 (PhyL). This enzyme (42 kDa) was optimally active at 70-75 C and pH 6.5-7.0.…”
Section: Recent Progress In Phytase Researchmentioning
confidence: 99%